Closed Reduction for Developmental Dysplasia of the Hip: Early-term Results From a Prospective, Multicenter Cohort. Issue 3 (March 2019) - Sankar, Wudbhav N.; Gornitzky, Alex L.; Clarke, Nicholas M.P.; Herrera-Soto, José A.; Kelley, Simon P.; Matheney, Travis; Mulpuri, Kishore; Schaeffer, Emily K.; Upasani, Vidyadhar V.; Williams, Nicole; Price, Charles T.
Abstract : Background: Closed reduction (CR) is a common treatment for infantile developmental dysplasia of the hip. The purpose of this observational, prospective, multicenter study was to determine the early outcomes following CR. Methods: Prospectively collected data from an international multicenter study group was analyzed for patients treated from 2010 to 2014. Baseline demographics, clinical exam, radiographic/ultrasonographic data, and history of previous orthotic treatment were assessed. At minimum 1-year follow-up, failure was defined as an IHDI grade 3 or 4 hip and/or need for open reduction. The incidence of avascular necrosis (AVN), residual dysplasia, and need for further surgery was assessed. Results: A total of 78 patients undergoing CR for 87 hips were evaluated with a median age at initial reduction of 8 months (range, 1 to 20 mo). Of these, 8 hips (9%) were unable to be closed reduced initially. At most recent follow-up (median 22 mo; range, 12 to 36 mo), 72/79 initially successful CRs (91%) remained stable. The likelihood of failure was unaffected by initial clinical reducibility of the hip ( P =0.434), age at initial CR ( P =0.897), or previous treatment in brace ( P =0.222). Excluding those hips that failed initial CR, 18/72 hips (25%) developed AVN, and the risk of osteonecrosis was unaffected by prereduction reducibility of the hip ( P =0.586), age at CR ( P =0.745), presence of an ossific nucleus ( P =0.496), or previous treatment in brace ( P =0.662). Mean acetabular index on most recent radiographs was 25 degrees (±6 degrees), and was also unaffected by any of the above variables. During the follow-up period, 8/72 successfully closed reduced hips (11%) underwent acetabular and/or femoral osteotomy for residual dysplasia. Conclusions: Following an initially successful CR, 9% of hips failed reduction and 25% developed radiographic AVN at early-term follow-up. History of femoral head reducibility, previous orthotic bracing, and age at CR did not correlate with success or chances of developing AVN. Further follow-up of this prospective, multicenter cohort will be necessary to establish definitive success and complication rates following CR for infantile developmental dysplasia of the hip. Level of Evidence: Level II—prospective observational cohort. Abstract : Supplemental Digital Content is available in the text.